Specific language impairment in Cypriot Greek: diagnostic issues - Theodorou, Eleni; Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2013)
Investigating children’s language skills in their native variety is of paramount importance. Clinical practices cannot be based on findings from languages or varieties which have different properties. This paper, after demonstrating the importance of investigating Specific Language Impairment (SLI) in Cyprus, assesses the feasibility of existing language assessments in Standard Modern Greek for the diagnosis of SLI in the Greek Cypriot context, for the children’s native variety of Cypriot Greek. In total, 16 children with SLI (5 to 9 years) and 22 age-matched typically language developing children participated in this study. However, given that not all stimuli in the Standard Greek versions were appropriate for Cypriot Greek-speaking children and because of cultural differences, the tools were adapted. Results showed that the assessment tools can accurately identify children with SLI from typically language developing peers with sensitivity and specificity when the comparison is between children that use the same variety
Keywords: Acquisition; Bilectalism; Diagnosis; Sensitivity; Specificity